2020
DOI: 10.3390/met10121696
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Alumina Inclusions in SWRS82B Steel by Adding Rare Earth Cerium

Abstract: The aluminum oxide inclusions in SWRS82B steel seriously affect the drawing performance of the steel strand. In this study, the influence of different additions of cerium (within the range of 0–0.034%) on the composition, morphology, size, number, and distribution of alumina inclusions was studied by scanning electron microscope and energy spectrum analyzer. The evolution of the composition of inclusions with different cerium additions was calculated based on classical thermodynamics and Factsage software calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Referring to Wang et al [26], the addition of rare earths increases the number density of inclusions, and, aside from that, the NMIs get smaller and spherical. Similar tendencies are observed by Li et al [31] and Wang et al [32]. In both studies, the irregularly shaped inclusions become more globular, and at low Cerium addition, their sizes decrease.…”
Section: Introductionsupporting
confidence: 88%
“…Referring to Wang et al [26], the addition of rare earths increases the number density of inclusions, and, aside from that, the NMIs get smaller and spherical. Similar tendencies are observed by Li et al [31] and Wang et al [32]. In both studies, the irregularly shaped inclusions become more globular, and at low Cerium addition, their sizes decrease.…”
Section: Introductionsupporting
confidence: 88%
“…In this method, NMIs are partially reduced due to the direct addition of rare earth elements (REEs) [17]. Several studies [18][19][20][21] have already managed to track the modification of deoxidation products, such as alumina NMIs, by adding La and Ce to the melt on industrial and laboratory scales. The benefit of this approach is the easy retrieval of REE-marked NMIs during automated scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM/EDS) analysis, since REEs appear brighter than the steel matrix in backscattered electron (BSE) images due to their higher atomic number [22].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the increasing demand for high-quality stainless steels, rare earth (RE) elements have attracted the attention of scholars due to their significant influence on the steel. [1][2][3][4][5][6][7][8] Inclusions in the steel, which have an important impact on the performance of the steel, [9][10][11][12] could be effectively modified by RE due to its strong affinity to oxygen and sulfur, [13][14][15][16][17][18] thus, influencing the property of the steel. Wang et al [19] found that an appropriate addition of RE reduced the susceptibility of pitting corrosion and improved the corrosion resistance of a duplex stainless steel.…”
Section: Introductionmentioning
confidence: 99%